Wave Energy Considerations for the Concept Design of Rock Armored Coastal Revetments (London Journal of Engineering Research, 2026)
Current practice for assessing toe scour, requisite armor mass and wave overtopping of rock-armored coastal revetments is based empirically on flume study data. Flume data are normalised, which is done to synthesize large datasets to a notionally common scale, making equations dimensionless. Factors that normalize laboratory data for developing current predictive formulae for scour, requisite armor mass and overtopping discharges are based universally on wave height and gravitational acceleration. This article utilizes data from comprehensive scale model studies of various rock armored coastal revetments from which current-practice formulae have been derived, but normalizing the laboratory data using factors based on wave energy rather than wave height alone. This has resulted in predictions of toe scour, requisite armor mass and average overtopping discharges that are more accurate than those from formulae in current use. The influence of wave period is examined with wave period being incorporated into predictive equations, resulting in further improvements. Some model and scale effects are identified, recommending further research.
Keywords: coastal revetment; overtopping discharge; requisite armor mass; rock armor; toe scour; wave energy.